Análisis comparativo de los programas matinales de televisión el club de la mañana y en contacto y el impacto que producen en la población femenina de la cooperativa Juan Montalvo - Román Ronquillo, Damaris Narcisa (2016)
Television programs such as morning programs are aimed at housewives and standout for their content with popular and novelties issues. The morning programs for their career highlights and audience are “En Contacto” from Ecuavisa and “El Club de la Mañana” from RTS. Nowadays, due to high competition some television morning shows have decreased their quality’s content, which, in some cases, are designed to generate only an increment of audience..….